Prediksi Penurunan Muka Tanah Menggunakan Teknik Differential Interferometic Synthetic Aperture Radar (Dinsar) Di Kota Makassar Indonesia - Haris, Nur Afdal (Jurnal Environmental Science, 2018)
Based ont the results of the ALOS Palsar image data analysis using the Differential Interferometric Synthetic Aperture Radar (DInSAR) technique on ENVI Sarscape application. The results of this study indicated that the amount of land subsidence in Makassar City from 2007-2011 was 5.8 cm with an average rate of land subsidence reaching 0.73 cm/year. Areas run into land subsidence are all sub-districts in Makassar City with variations land subsidence values from 0.09 – 5.8 cm.